Renewable Energy Transformation or Fossil Fuel Backlash Vested Interests in the Political Economy - Moe, Espen; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Renewable energy is rising within an energy system dominated by powerful vested energy interests in fossil fuels, nuclear and electric utilities. Analyzing renewables in six very different countries, the author argues that it is the extent to which states have controlled these vested interests that determines the success or failure of renewables.
Keywords: Environment; Energy policy; Energy and state; Political economy; Energy industries; Sustainable development; Environmental policy; Environmental economics; Environment; Environmental Politics; Sustainable Development; Environmental Economics; Energy Policy, Economics and Management; Political Economy; Energy Economics; Electronic books